Permanent health education in elderly care: integrative review (PerCursos, 2023)
The increase in the elderly population has changed the demographic and epidemiological profile of Brazilian society with repercussions on all public policies. In the Unified Health System (SUS), it requires reorganization of services to respond to the diversity of demands aimed at promoting and recovering health in all life cycles. Faced with this new reality, it is necessary to encourage new skills in professionals to develop care practices that focus on the multidimensional aspects inherent in the health of the elderly. The implementation of Continuing Education can favor the reconstruction of the concept of health for the elderly and the construction of a praxis that promotes an expanded clinic, oriented towards meeting the peculiarities of this population segment. Method: This is an integrative review study with the objective of knowing the scientific production on permanent education in the health care of the elderly in Brazil, from 2004 to 2020, developed in the primary health care of the SUS. After analyzing the scientific production obtained from multidisciplinary and health sciences databases, eight publications were selected for this study. Results: It was identified that women, nurses, affiliated with higher education institutions, stand out in the study of EPS in health care actions for the elderly. There is also little knowledge of professionals about the aging process, which is associated with work overload, turnover of PHC professionals, lack of prioritization of management on the health of the elderly and health education processes; make it difficult to carry out EPS in the territories, harming the development of the expanded clinic in the health of the elderly population.
Keywords: permanent health education; primary health care; health of the elderly